Pengaruh Kompensasi Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Moderasi Pada PT Sukses Mitra Sejahtera Kabupaten Kediri - Mohammad Khofi Anazail; Ahmad Jauhari; Nur Hidayati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The purpose of this research is to determine the use of work motivation as a moderating variable in the influence of compensation on employee performance at PT Sukses Mitra Sejahtera located in Kediri Regency. This research uses quantitative methodology and the research sample consists of 87 employees. Data analysis was carried out using Smart PLS software. The research results show that there is a significant influence between compensation on employee performance at PT Sukses Mitra Sejahtera as evidenced by the T-statistic value of 2.430 > 1.96 and the P-value of 0.015 < 0.05. Work motivation does not significantly moderate the interaction between compensation variables and employee performance, shown by T-statistic 1.779 < 1.96 and P-value 0.075 > 0.05.